Genome-wide analysis of ethylene-response factor family in adzuki bean and functional determination of VaERF3 under saline-alkaline stress - Li, Wei-Yu (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.